Evaluation of The Provision of Pedestrian Paths for Persons with Disabilities in Temanggung Regency - Selin Dama Priyanti; Amin Pujiati (Journal of Economics and Business, 2021)
This study aims to determine the application of the Regulation of the Minister of Public Works of the Republic of Indonesia Number 30 / PRT / M / 2006 concerning Facilities and Accessibility in Buildings and Environment (construction of pedestrian paths) for persons with disabilities in Temanggung Regency. The number of respondents used was 98 people. The analytical tool used in this research is Gap Analysis. The results of the gap analysis research show that the percentage of the provision of pedestrian paths for people with disabilities in Temanggung Regency is 33.33%, which means that the implementation of the provision of pedestrian paths for people with disabilities in Temanggung district has been poor.